Developing State Capacity: The Missing Variable for Corporate Social Responsibility?. Issue 3 (September 2020) - Hira, Anil
The emergence of "corporate social responsibility" (CSR) among Western multinationals reflects doubts about governments in the South to regulate production as well as a vacuum of global regulatory capacity and authority. In response to criticism, media shaming, and protests from NGOs and civil society organizations centered around labor and environmental concerns, corporations began to organize a global public regime, as reflected in the Global Compact, in the 1990s. CSR is the focus of both national and global agreements, with companies starting to work with international organizations and NGOs in emerging CSR "mixed regimes." Yet there are inherent contradictions in both CSR and mixed regimes, ones that can only be resolved by reasserting a more activist role for the developing state.